Further evidence to support the melanocytic origin of MDA-MB-435. Issue 5 (1st October 2002) - Ellison, G; Klinowska, T; Westwood, R F R; Docter, E; French, T; Fox, J C
Abstract : Background/Aims: Until recently, the cell line MDA-MB-435 was widely accepted as originating from a breast cancer. However, microarray derived data have suggested that this cell line may in fact originate from an occult melanoma. This study was designed to investigate this hypothesis further. Methods: Quantitative reverse transcription polymerase chain reaction and immunohistochemistry were used to investigate the tissue of origin of two sublines of MDA-MB-435 (MDA-MB-435 S and MDA-MB-435 HGF). The expression of a panel of genes typical of breast cells or melanocytes was analysed. Results: The MDA-MD-435 cell lines expressed none of the genes characteristic of breast cancer cells but did express several genes commonly expressed by melanocytes. Conclusions: These results strongly suggest that MDA-MB-435 is indeed of melanoma origin.